'Ngondek' Celebration in Variety Shows on Television: A Critical Discourse Analysis - Utami, Dewi; Suwarso, Widha Anistya (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
Variety show Ms.Queen on the NET television station March 22, 2022 "Mang Osa Refuses to be in television show when viral", explicitly discusses that ‘ngondek’ is funny,liked, and makes someone viral and popular, which is the dream of most young people in the era of social media like now. This show is violating broadcasting ethics in Indonesia and can trigger imitation from the audience, especially children and adolescents who watch this program and have a positive interpretation for this show. From this, the researcher is interested in discussing further the matter of ‘ngondek’ men in the show to find out what discourse is actually offered by television to the audience, and how it is done. The researcher uses the critical discourse analysis technique of Sarah Mills who believes that texts are the result of negotiations between the writer and the reader. The results of this research show that there are clearly legible main actors in the text, namely the television institution (in this case the program creative team) who holds the power to determine the subject-object positions. By accepting to come at Ms.Queen, means that consciously or not, MO places himself as an object. Overall, the author of the text tries to present a woman's point of view to normalize Irfan's and MO's feminine performance which is difficult for a male point of view to accept. There is a text that is deliberately written that a man with a feminine performance is a funny, entertaining, and easily popular figure where the audience is directed to follow the same perspective. This also gives the same definition to other ‘ngondek’ men to be interpreted in the same way by the audience.